2007
DOI: 10.3758/bf03193506
|View full text |Cite
|
Sign up to set email alerts
|

Realizing complex delayed intentions in young and old adults: The role of planning aids

Abstract: Although it has been suggested that the delayed realization of intended actions should benefit from appropriate intention planning, empirical evidence on this issue is scarce. In three experiments, we examined whether and which planning aids provided in the intention formation phase affect delayed intention realization in young and old adults. One finding was that intention planning directly affected delayed intention realization: instructing participants to include the cue for appropriate intention initiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 41 publications
(53 reference statements)
2
45
0
4
Order By: Relevance
“…Consequently, at least some of the participants in this instructional condition might not spontaneously form a strong link between the target cue and the intention, a link that is explicitly emphasized in the implementation intention condition. Kliegel, Martin, McDaniel, Einstein, and Moor (2007) have provided evidence that participants' spontaneous prospective memory encodings when given typical prospective memory instructions do not necessarily focus sharply on the target-cue-intention link (see also Cohen & Gollwitzer, 2008;McDaniel, Howard, & Butler, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, at least some of the participants in this instructional condition might not spontaneously form a strong link between the target cue and the intention, a link that is explicitly emphasized in the implementation intention condition. Kliegel, Martin, McDaniel, Einstein, and Moor (2007) have provided evidence that participants' spontaneous prospective memory encodings when given typical prospective memory instructions do not necessarily focus sharply on the target-cue-intention link (see also Cohen & Gollwitzer, 2008;McDaniel, Howard, & Butler, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, in an ill-structured multi-task prospective memory paradigm requiring participants to remember several intentions at once, participants were instructed to develop a plan that explicitly included a cue determining when they intended to start working on the single prospective memory tasks. Kliegel et al (2007) observed that the structure of successful plans was similar to implementation intentions, which take the form ''If situation X arises, then I will perform behaviour Y'' (Gollwitzer 1999). Implementation intentions describe a means of resolving the discrepancy between one's current and desired behaviour by specifying when, where, and how a goal-directed response will be executed.…”
Section: Introductionmentioning
confidence: 99%
“…Kliegel et al 2002Kliegel et al , 2003Kliegel et al , 2007. Kliegel et al (2007) showed that certain planning aids improved older adults' prospective memory performance to a level equal to that found in young adults. Specifically, in an ill-structured multi-task prospective memory paradigm requiring participants to remember several intentions at once, participants were instructed to develop a plan that explicitly included a cue determining when they intended to start working on the single prospective memory tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Kliegel et al (2007) have recently shown that improving old adults' intention formation may lead to an equal prospective memory performance in young and old adults. Thus, the difficulties of old adults in the realization of delayed intentions might, at least in part, be due to a reduced strategic encoding capability and suggest age-related differences between young and old adults in the neural correlates of intention formation.…”
Section: Differential Compensational Mechanisms Across the Lifespanmentioning
confidence: 99%